Tumor Differentiation is Correlated with Estrogen Receptor Beta (ERβ) Expression but Not with Interleukin-6 (IL-6) Expression in Colorectal Carcinoma - Imelda Theodora; I Ketut Sudiana; Vicky Sumarki Budipramana; Ferdinand Erwin; Sianty Dewi; Bernadette Dian Novita (Indonesian Biomedical Journal)
BACKGROUND: Colorectal carcinoma (CRC), the third most common malignant disease worldwide, is associated with estrogen receptor β (ERβ) and interleukin-6 (IL-6). ERβ is known to down-regulate IL-6 in prostate cancer, lung carcinoma, and CRC cell lines; however, its effect on human with CRC remains unclear. Therefore, this study was conducted to investigate the association between ERβ and IL-6 expressions with the clinicopathological features of CRC.